1999
DOI: 10.1002/(sici)1096-8628(19990917)86:3<294::aid-ajmg20>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Two sibs with Malpuech syndrome

Abstract: We report on two Italian brothers with facial clefting, hypertelorism, urogenital anomalies including micropenis, shawl scrotum, hearing loss, caudal appendage, and umbilical hernia. We have evaluated the two cases as Malpuech syndrome. This is an extremely rare autosomal recessive syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…This combination of symptoms is not found in Malpuech or Michels syndrome, although in some patients single symptoms have been found to be present; -umbilical depressions can be present in all entities, but in the patients reported by Carnevale et al [1989], Mingarelli et al [1996], and Guion-Almeida and Rodini [1995], a diastasis recti is also almost invariably present. The umbilical abnormalities are variable and by far the most expressed in the patients reported by Carnevale et al [1989]; -caudal appendages have been found in half of the patients with Malpuech syndrome, but not in any of the other entities; -abnormal elbow mobility, with or without detectable radio-ulnar synostosis, has been found in all entities except for Malpuech syndrome; [Malpuech et al, 1983;Chinen and Naritomi, 1995;Guion-Almeida, 1995;Crisponi et al, 1999;Kerstjens-Frederikse et al, 2005]. b [Michels et al, 1978;Cunniff and Jones, 1990;De La Paz et al, 1991;Titomanlio et al, 2005].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This combination of symptoms is not found in Malpuech or Michels syndrome, although in some patients single symptoms have been found to be present; -umbilical depressions can be present in all entities, but in the patients reported by Carnevale et al [1989], Mingarelli et al [1996], and Guion-Almeida and Rodini [1995], a diastasis recti is also almost invariably present. The umbilical abnormalities are variable and by far the most expressed in the patients reported by Carnevale et al [1989]; -caudal appendages have been found in half of the patients with Malpuech syndrome, but not in any of the other entities; -abnormal elbow mobility, with or without detectable radio-ulnar synostosis, has been found in all entities except for Malpuech syndrome; [Malpuech et al, 1983;Chinen and Naritomi, 1995;Guion-Almeida, 1995;Crisponi et al, 1999;Kerstjens-Frederikse et al, 2005]. b [Michels et al, 1978;Cunniff and Jones, 1990;De La Paz et al, 1991;Titomanlio et al, 2005].…”
Section: Discussionmentioning
confidence: 93%
“…For Malpuech syndrome, data from all earlier reported patients were used [Malpuech et al, 1983;Chinen and Naritomi, 1995;Guion-Almeida, 1995;Crisponi et al, 1999;Kerstjens-Frederikse et al, 2005], although it seems well possible that Patient 2 reported by Guion-Almeida has in fact Wolf-Hirschhorn or Pitt-Rogers-Danks syndrome [Selicorni and Faravelli, 2000]. The single patient reported in an abstract [Hall, 2004] could not be used due to lack of sufficiently detailed data.…”
Section: Discussionmentioning
confidence: 99%
“…On pictures, mild blepharophimosis may be present, although it is not mentioned in the reports. Crisponi et al [1999] reported further sibs with convincing facial appearance and normal intelligence. Review of the literature on Malpuech is difficult, as several patients appear to have a phenotype only loosely related to the original report, making tabular analysis of signs misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Malpuech syndrome is a rare multiple congenital anomaly syndrome. The incidence is unknown, but at least 12 patients worldwide are reported to have this condition (2). There is often difficulty regarding a definite clinical diagnosis.…”
mentioning
confidence: 99%
“…A genetic locus has not been determined, but abnormalities in the PAX2gene, the ROR2 gene, and the P63 gene are believed to be involved in the generation of this syndrome (3). The facial features of this disorder are typically cleft lip and palate, hypertelorism, ptosis and malar hypoplasia, micrognathia and prominent dentition (2). Affected children may also present with omphalocele, umbilical hernia, renal aplasia, undescended testis, micropenis, caudal appendage and a sacral dimple suggestive of spina bifida occulta (2).…”
mentioning
confidence: 99%